2014
DOI: 10.1177/016146811411600605
|View full text |Cite
|
Sign up to set email alerts
|

Heritage, History, and Identity

Abstract: Background/Context Prior research indicates that students’ ethnic, religious, national, and racial identities often impact their interest in, emotional connection to, and knowledge about histories specific to those groups with which they identify. Purpose/Objective/Research Question/Focus of Study (a) What meaning do students attach to events with which they have a heritage connection? (b) How do students’ identities impact their connection to, interest in, and understanding of events with which they have a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Cheng et al, 2014; Cui, Fitzgerald, & Donovan, 2014; Devos & Yokoyama, 2014; Gartner et al, 2014; T. L. Lee, Wilton, & Kwan, 2014; Levy, 2014; Ocampo, 2014; Roberts, Cha, & Kim, 2014), the buffering role of ethnic identity in Asian American adolescents’ lives (Stein et al, 2014), and the effects of social justice-oriented youth programs on racial and ethnic identities for Asian American youth (Suyemoto, Day, & Schwartz, 2015). A two-wave longitudinal study demonstrated the moderating role of ethnic identity (belonging and exploration) on the effects of economic stress (but not perceived ethnic discrimination) on mental health outcomes (depressive symptoms and self-esteem) in a sample of Asian American adolescents from an emerging immigrant community (Stein et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al, 2014; Cui, Fitzgerald, & Donovan, 2014; Devos & Yokoyama, 2014; Gartner et al, 2014; T. L. Lee, Wilton, & Kwan, 2014; Levy, 2014; Ocampo, 2014; Roberts, Cha, & Kim, 2014), the buffering role of ethnic identity in Asian American adolescents’ lives (Stein et al, 2014), and the effects of social justice-oriented youth programs on racial and ethnic identities for Asian American youth (Suyemoto, Day, & Schwartz, 2015). A two-wave longitudinal study demonstrated the moderating role of ethnic identity (belonging and exploration) on the effects of economic stress (but not perceived ethnic discrimination) on mental health outcomes (depressive symptoms and self-esteem) in a sample of Asian American adolescents from an emerging immigrant community (Stein et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…First, we found some evidence that students' heritage influences their trust of the documents in the Mexicans and Mexican Americans task. Previous studies (e.g., Levy, 2014;Peck, 2010;Rameriz, 2012) found that students' identities can be a powerful factor in how they make sense of the past. In this study, students had different criteria for trustworthiness of sources for the two tasks, even for the same kinds of sources.…”
Section: Grounding Our Findings In the Literaturementioning
confidence: 99%
“…Levy's (2014) study of Hmong, Chinese, and Jewish students in US schools examined how the students connected to topics to which they could have had a heritage connection (where family members could have been involved, but not the students). Levy discovered that almost all of the students were able to combine heritage knowledge (often acquired from hearing family stories) and school/official knowledge to “grapple with conflicting perspectives and deepened both their understanding of and their identification with these seminal events” (p. 25).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations